1987
DOI: 10.1210/endo-120-6-2251
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Receptors for Insulin-Like Growth Factor I, Platelet-Derived Growth Factor, and Fibroblast Growth Factor in Rat Aortic Cells

Abstract: Serum contains various growth factors which regulate the proliferation of cells. We investigated the growth of cultured arterial smooth muscle cells under the influence of insulin-like growth factor I (IGF I), fibroblast growth factor (FGF), and platelet-derived growth factor (PDGF), and examined the effect of these growth factors on the binding of [125I] IGF I and on the binding of [125I]PDGF to these cells. IGF I, FGF, and PDGF stimulated [6-3H]thymidine incorporation into DNA of confluent cultures of cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(24 citation statements)
references
References 54 publications
(52 reference statements)
0
24
0
Order By: Relevance
“…Thus, both PDGF and angiotensin II upregulate IGF I receptors on VSMC (40,41) and their mitogenic effects are blocked by anti-IGF I antiserum (6,14). The concept that upregulation of IGF I receptors may serve a key function in mitogenic responses to agonists is supported by our recent demonstration that VSMC mitogenic responses to angiotensin II are almost completely inhibited by downregulation of IGF I receptors (31).…”
Section: Discussionmentioning
confidence: 83%
“…Thus, both PDGF and angiotensin II upregulate IGF I receptors on VSMC (40,41) and their mitogenic effects are blocked by anti-IGF I antiserum (6,14). The concept that upregulation of IGF I receptors may serve a key function in mitogenic responses to agonists is supported by our recent demonstration that VSMC mitogenic responses to angiotensin II are almost completely inhibited by downregulation of IGF I receptors (31).…”
Section: Discussionmentioning
confidence: 83%
“…The IGF-IR plays a central role during the cell cycle, as demonstrated by the fact that overexpression of IGF-IR abrogates requirements for exogenous growth factors (4). In vascular smooth muscle cells (VSMCs),the IGF-IR mediates the mitogenic effects of various growth factors such as platelet-derived growth factor, endothelial growth factor, fibroblast growth factor ␤, thrombin, and angiotensin II, consistent with an important role in cardiovascular growth responses (5)(6)(7)(8). A variety of studies have shown that relatively small changes in IGF-IR expression have important proliferative or antiproliferative effects (9 -11).…”
Section: Insulin-like Growth Factor I (Igf-i)mentioning
confidence: 99%
“…Both bFGF and PDGF synergize with IGF-I in their biological actions (25,26). The results of the present study suggest that one mechanism may be the increased expression of the IGF-I receptor by these growth factors.…”
Section: Differential Regulation Of Igf-i Receptor Gene 4667mentioning
confidence: 99%